Effect of milling time on mechanical and physical behavior of ALMMC reinforced with AL2O3 - Suhaimi, Md Yusoff (2008)
This thesis is to investigate the effect of milling time to the mechanical and physical properties Aluminum metal matrix composite reinforced with alumina. The objective of this thesis is to study the effect of milling time on mechanical and physical properties of powder materials. This thesis also to characterize the hardness and microstructure of Aluminum MMC produced by reinforced aluminum with alumina using powder metallurgy process. The thesis describes the powder metallurgy process to produce Al MMC reinforce with Al2O3. The powder metallurgy process consist of three main process which is milling process, compaction process and sintering. The milling process has big influence on the characteristic of powder materials, due to particle deformation followed by welding and fracturing particles. Mechanical milling is a process involving repeated deformation, welding and fracture. The mechanically milled show finer and better distribution of reinforcement particle what lead to better mechanical properties of obtained product. The results are increasing the milling time significant to improve the mechanical and physical properties of the Aluminum metal matrix composite produced.